Políticas urbanas de patrimonialização e consumo : a paisagem cultural do Rio de Janeiro - Souza, Eder Claudio Malta (2015)
This thesis analyzes the city patrimonialization process of Rio de Janeiro and investigates the Dossier “Rio de Janeiro: Carioca Landscapes between the mountain and the sea”, coordinated by Iphan and approved by Unesco as first city Cultural Heritage in Cultural Landscape category, inscribed from the relationship between the landscape and the carioca urban culture. The research hypothesis concerns that patrimonialization symbolically values the cultural landscape and democratizing the spaces to nominate the representation spaces of affective and identity values of the city, but his nomination as world heritage stems from the inscription of properties and consumer places on the delimitation of the site. The central argument is that the patrimonialization of Rio de Janeiro aims at recomposition of identity and urban image built around the epithet “Wonderful City”, which lost the symbolic efficacy as a tourist attraction due to exhaust the city’s image, insofar as the strong publicity of socio-spatial differences, the conflictuality, social inequality, slums and urban violence become a counter-landscape of traditional places of Rio public visibility. Therefore, it proposed to discuss how the sociocultural landscape is incorporated in the search for a new image and conforms as a desirable future of social, environmental, economic and cultural sustainability of the city.